2021
DOI: 10.1177/21925682211024573
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Steroid Injections Are Not Effective for Prevention of Surgical Treatment of Degenerative Cervical Myelopathy

Abstract: Study Design: Retrospective cohort study. Objective: The objective of this study is to determine how often patients with degenerative cervical myelopathy (DCM) and initially treated with cervical steroid injections (CSI) and to determine whether these injections provide any benefit in delaying ultimate surgical treatment. Methods: All patients with a new diagnosis of DCM, without previous cervical spine surgery or steroid injections, were identified in PearlDiver, a large insurance database. Steroid injection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…To the best of our knowledge, the present study is the first to evaluate the effect of cervical canal stenosis grade on epidural steroid injection therapy. Manzur et al (17) evaluated the data of 244 patients with cervical myelopathy (Grade 3 according to the classification of Kang et al ( 6)) and reported that epidural steroid injections did not delay surgical treatment. In our clinical practice, we refer patients with myelopathy in cervical spinal MRI and severe symptoms to surgical treatment, as their condition may be progressive.…”
Section: Resultsmentioning
confidence: 99%
“…To the best of our knowledge, the present study is the first to evaluate the effect of cervical canal stenosis grade on epidural steroid injection therapy. Manzur et al (17) evaluated the data of 244 patients with cervical myelopathy (Grade 3 according to the classification of Kang et al ( 6)) and reported that epidural steroid injections did not delay surgical treatment. In our clinical practice, we refer patients with myelopathy in cervical spinal MRI and severe symptoms to surgical treatment, as their condition may be progressive.…”
Section: Resultsmentioning
confidence: 99%
“…Into this discussion has stepped a team from Philadelphia (Pennsylvania, USA) who have carried out a retrospective cohort study of 686 patients treated for DCM, comparing the outcomes in those who received steroid injections with those who did not. 2 The findings revealed that cervical steroid injections did not effectively prevent the need for surgical treatment in patients with DCM. No significant difference in the rates of surgical intervention between the group that received cervical steroid injections and the group that did not was observed, suggesting that the use of cervical steroid injections as a standalone treatment for DCM is not supported.…”
Section: Steroid Injections Are Not Effective In the Prevention Of Su...mentioning
confidence: 95%
“…Late-onset neurological deterioration may also occur despite adequate mechanical decompression [ 133 , 134 ]. There is insufficient evidence to support the long-term efficacy of non-operative management approaches for DCM such as physiotherapy, nutritional supplementation, use of analgesics and non-steroidal anti-inflammatory drugs (NSAIDs), cervical steroid injections (CSIs), traction, and acupuncture [ 10 , 135 137 ]. Few DCM-related therapeutics have undergone clinical testing.…”
Section: Potential Therapeutic Strategies To Ameliorate Bscb Disruptionmentioning
confidence: 99%